Penegakan Hukum terhadap Kekerasan pada Anak Menurut Hukum Adat Siak Sri Indrapura - Rani, Nabella Puspa (Magister (S2) Ilmu Hukum Fakultas Hukum Universitas Riau, 2018)
The purpose of this paper is to determine law enforcement against child abuse according to the customary law of Siak Sri Indrapura. Bab Al-Qawaid is written laws used to regulate in the area of the Siak Sri Indrapura Kingdom. Article eight in Bab Al-Qawaâid specifically regulate the prohibition of child abuse. Factors of law enforcement against child abuse in Siak Sri Indrapura can be seen from factors of legal, law enforcer, facilities or support facilities, community and culture. Another factor is the political factor of customary law in Siak Sri Indrapura that customary law does not become the main reference in the resolution of the law against child abuse, due to the dominance of national law for customary law.